2018
DOI: 10.5826/dpc.0801a14
|View full text |Cite
|
Sign up to set email alerts
|

Patient with confirmed leopard syndrome developing multiple myeloma

Abstract: LEOPARD syndrome, also known as Gorlin syndrome II, cardiocutaneous syndrome, lentiginosis profusa syndrome, Moynahan syndrome, was more recently coined as Noonan syndrome with multiple lentigines (NSML), inside the RASopathies. Historically, the acronym LEOPARD refers to the presence of distinctive clinical features such as: lentigines (L), electrocardiographic/conduction abnormalities (E), ocular hypertelorism (O), pulmonary stenosis (P), genital abnormalities (A), retardation of growth (R), and sensorineura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, NS-ML clinically resembles NS, raising a long debated question why both GOF and LOF mutations of SHP2 result in similar clinical manifestations (Edouard et al, 2007;Zheng et al, 2009). Remarkably, both NS and NS-ML are predisposed to an elevated risk of malignancy (Cheng et al, 2013;Colmant et al, 2018;Laux et al, 2008;Liu et al, 2016;Tartaglia et al, 2004). These observations suggest that LOF mutations of SHP2 may, similarly as GOF mutations, also acquire capability to activate the RAS-MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 93%
“…However, NS-ML clinically resembles NS, raising a long debated question why both GOF and LOF mutations of SHP2 result in similar clinical manifestations (Edouard et al, 2007;Zheng et al, 2009). Remarkably, both NS and NS-ML are predisposed to an elevated risk of malignancy (Cheng et al, 2013;Colmant et al, 2018;Laux et al, 2008;Liu et al, 2016;Tartaglia et al, 2004). These observations suggest that LOF mutations of SHP2 may, similarly as GOF mutations, also acquire capability to activate the RAS-MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 93%
“…Cheng et al reported a 24-year-old female who developed a scalp melanoma and had a germline heterozygous PTPN11 missense mutation [8]. Colmant et al reported a 62-year-old male with NSML and a mutation in the PTPN11 gene who developed four superficial spreading melanomas (three were achromic or hypochromic) and three atypical lentiginous hyperplasias [1]. García-Gil et al reported a 44-year-old male with NSML confirmed by the genetic study of a mutation in heterozygosity in the PTPN11 gene who developed a melanoma at the dorsal level of the trunk [9].…”
Section: Discussionmentioning
confidence: 99%
“…LEOPARD syndrome (LS), currently termed Noonan syndrome with multiple lentigines ( NSML), is a complex, dysmorphogenetic, multisystemic disorder of autosomal dominant heredity and variable penetrance and expressivity [1,2]. Its prevalence remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations